Erratum to: Search for dark matter and unparticles in events with a Z boson and missing transverse momentum in proton-proton collisions at √s=13 TeV (JHEP, (2017), 9, (106), 10.1007/JHEP09(2017)106) - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (Springer Verlag, 2018)
In the original paper, figure 10 was incorrect. The correct figure is shown below. Additionally, the unparticle entries in table 3, as well as figure 4 and 5 were labelled with incorrect values of ΛU.